An Improved Golden Ball Algorithm for the Vehicle Routing Problem with Simultaneous Pickup and Delivery - Ruttanateerawichien, Kanjana; Kurutach, Werasak (2018 IEEE ACIS 17th International Conference on Computer and Information Science (ICIS), 2018)
A Golden Ball (IGB) algorithm was improved for the well-known vehicle routing problem, which simultaneously considers the customer demand from both delivery and pickup orders. The objective of this problem was to determine the optimal set of routes to totally satisfy both the delivery and pickup demand of the customer population. In this paper, the Golden Ball (GB) algorithm was improved using intra-move improvement algorithms modify process selection players and coaching procedure. The aim was to find the solution that minimizes the total cost. Computational results showed that the IGB algorithm was competitive and outperforms the Golden Ball (GB) algorithm in all directions. Moreover, the best known solutions were also obtained in 67.43% of tested instances (19 out of 28).